Acupuncture for acute moderate thalamic hemorrhage: randomized controlled trial study protocol. Issue 1 (December 2017) - Wang, Chengwei; You, Chao; Ma, Lu; Liu, Mengyue; Tian, Meng; Li, Ning
Abstract Background Thalamic hemorrhage (TH) is a neurological insult with a high rate of morbidity and mortality. Moderate TH (10–30 ml) accounts for more than half of all TH. Treatment remains controversial. The role of acupuncture in patients with moderate TH is not clear. Methods We will conduct a single-center, randomized, parallel group, and assessor-blinded clinical trial. A total of 488 patients with moderate TH will be randomly assigned to one of eight groups: 10–15 cc left sided TH study group (N = 61) and a corresponding control group (N = 61), 10–15 cc right sided TH study group (N = 61) and a corresponding control group, 15–30 cc left sided TH study group (N = 61) and a corresponding control group (N = 61), and 15–30 cc right sided TH study group (N = 61) and a corresponding control group. Study groups will receive acupuncture in addition to standard treatment, while control groups will receive standard treatment alone. The primary outcome will be change in National Institutes of Health Stroke Scale scores at 30 and 90 days after TH. The secondary outcomes will be death or major disability, defined as a score of 3 to 6 on the modified Rankin scale (in which a score of 0 indicates no symptoms, a score of 5 indicates severe disability, and a score of 6 indicates death) at 90-days, need for surgery at 30-days, Glasgow Outcome Scale (GOS) score at 90-days following TH onset, and the results of several additional group specific tests. The rate of adverse events will then be compared between the groups. Discussion This study will attempt to answer the question of whether or not acupuncture can improve neurologic outcome following moderate TH. Trial registration Chinese clinical trial registry(ChiCTR-IOR-16008362)